NEW PHARMACEUTICALS - THE IMPORTANCE OF SERENDIPITY - Đurić, Larisa; Milanović, Maja; Milošević, Nataša; Milić, Nataša (Medicinski časopis, 2021)
The key elements of serendipity are luck and contemplation. The discovery process includes the recognition of the finding potential based on the knowledge and experience. Serendipitous discoveries are common in biomedical sciences. The significant number of pharmaceuticals is the result of serendipity. Drugs belonging to antimicrobial agents, central nervous system active substances as well as antitumor agents, gained the great benefit from the serendipity conditions. Besides the traditional, irrational approach in the drug design, serendipitous discoveries have also played role in modern strategies, such as the drug repositioning and the development of multi-target antitumor agents. Serendipitous drugs discoveries can be classified as laboratory or clinical, depending on the drug development stage and the circumstances under which the combination of unforeseen events, the knowledge and skills of the researcher occurred. The discovery of new drug is impossible without outstanding science as well as the dedication, freedom, and open-mindedness of the researcher to act, think, take a risk and challenge dogmas.